Bacteriological quality and associated risk factors of drinking water in Eastern zone, Tigrai, Ethiopia, 2019 - Aderajew Gebrewahd (Tropical Diseases, Travel Medicine and Vaccines, 2020)
Abstract Background Access to safe drinking water is one of the basic human rights and is critical to health. However, much of the world’s population lacks access to adequate and safe water. Approximately 884,000, 000 people in the world still do not get their drinking water from safe sources; Sub-Saharan Africa accounts for over one third of this number. It is estimated that 80% of all illnesses in the world are related to use of unsafe and contaminated water. Methods A cross-sectional study was conducted from August 1st 2017 to July 30th 2018 in three randomly selected woreda (districts) of Eastern Zone Tigrai. Water samples were examined for total coliforms and thermotelorant coliforms using the most probable number method. Standard biochemical testing was performed on samples that tested positive to identify the genus of bacteria. The contaminant risk of water sources were assessed using the sanitary inspection checklist of the World Health Organization. The results were interpreted using World Health Organization guidelines for drinking water quality. Data was collected using laboratory checklist and sanitary inspection check list. It was entered, cleared and analyzed using SPSS version 21.0 and a variable having a P < 0.05 was considered as statistically significant in all tests. Results A total of 290 drinking water samples were analyzed for bacteriological quality. A total of 32.4% (n = 94) of water sources showed contamination with faecal and total coliforms. Of these 3.4% (n = 10) samples were contaminated with total coliforms and 29% (n = 84) contaminated with faecal coliforms. The leading water contaminant organisms were Escherichia coli (62.4%), Legionella species (8.5%), and Shigella species (7.5%) respectively. Based on WHO criteria, 15% of water sources were grouped in the very high risk group. Animal excreta and inadequate fencing of water sources were significantly associated with water contamination rate. Conclusion Our findings suggest that most water sources in woredas of Eastern Tigrai are contaminated by faecal coliforms. Therefore, regular sanitary inspection, bacteriological analysis, and adequate fencing should be mandatory to protect drinking water sources from faecal contamination.